Syndicate Size, Spreads, and Market Power during the Introduction of Shelf Registration - FOSTER, F. DOUGLAS (Journal of Finance, 1989)
ABSTRACT The introduction of shelf registration in 1982 is used to examine the extent of price‐taking behavior among investment banks. Changes in underwriting syndicates are compared with the concomitant adjustment in underwriting spreads and management fees. The evidence is consistent with higher organizing costs and/or market power in the underwriting syndicate. Evidence on the components of the spreads and syndicate composition during the introduction of shelf registration is also presented.